Misreading Brave New World. Issue 3 (2015) - Carbonell, Curtis D.
Abstract : Biocritics argue that science and technology may present devastating political problems for humans in the coming century. They bolster their claims by misreading Aldous Huxley's dystopian novel, Brave New World, to present an essentialist's notion of human nature. This article challenges these misreadings via the embodiment theory of N. Katherine Hayles to argue that Huxley critiques the scientifically organized World State, so feared by biocritics, but also critiques the primitive world of John the Savage. Thus, Huxley reminds us that both unappealing possibilities are problems and that any use of Brave New World as a warning against untrammeled biotech should admit this contradiction. It solves the novel's inescapable dilemma of Cartesian subjectivity by valorizing embodied action and living.